Hepatitis C Treatment at a Rural Navajo Health Clinic Using Project ECHO - Anna R Nance; Lori S Saiki; Elizabeth G Kuchler; Conni DeBlieck; Susan Forster-Cox (Online Journal of Rural Nursing and Health Care, 2020)
Purpose: Hepatitis C incidence is higher among American Indian/Alaskan Native populations than any other racial or ethnic group in the United States. Chronic Hepatitis C complications include cirrhosis of the liver, end stage liver disease, and hepatocellular cancer. Direct acting antiviral treatment taken orally results in > 90% cure, yet rural primary care providers lack the training and confidence to treat and monitor patients with chronic Hepatitis C. Rural patients are reluctant to travel to urban areas for Hepatitis C treatment. Project ECHO is an innovative tele-mentoring program where specialists mentor primary care providers via videoconferencing to treat diseases they would otherwise be unable to manage. The purpose of this quality improvement project was to increase Hepatitis C treatment at a rural Navajo health clinic through partnership with Project ECHO specialists.